The influence of anthropometric characteristics on swimming speed in adolescent swimmers - Jovica Peulić; Anja Obradović; Mila Vukadinović Jurišić; Jelena Obradović (University of Novi Sad, Faculty of Sport and Physical Education, 2023)
Swimming speed depends on anthropometric characteristics, biomechanics factors, physical fitness, physiological components, and genetics. Therefore, this study aimed to identify which anthropometric characteristics influence swimming speed in adolescent competitive swimmers. Thirty-eight male swimmers (aged 16.94 ± 0.8 years; body height: 178.3 ± 5.4 cm; body weight 67.7 ± 9.6 kg) and thirty-five female swimmers (aged 17.12 ± 0.7 years; body height: 175.1 ± 6.6 cm; body weight 59.9 ± 7.1 kg) participated in the study. All swimmers have competed at the national level in Serbia for at least three years and have at least five years of training experience. Fifteen variables were measured: arm length, hand length, leg length, foot length, seat height, wrist diameter, ankle joint diameter, elbow diameter, chest circumference, triceps skinfold, forearm skinfold, abdominal skinfold, subscapular skinfold, thigh skinfold, calf skinfold. The measurements were taken by the Martin anthropometer, Omron digital scale BF511, and John Bull caliper. Swimming speed was measured during 50-m and 100-m front crawl swimming. Multiple regression analysis revealed that arm length, wrist diameter, and chest circumference, all together, accounted for 77% of 100-m front crawl swimming speed in male swimmers, while abdominal skinfold accounted for 90% of 100-m front crawl swimming speed in female swimmers. Results showed that anthropometric characteristics could not account for adolescent swimmers' 50-m front crawl swimming speed. However, anthropometric characteristics can influence the result in swimming (100-m front crawl swimming speed) in adolescents and thus should be considered a diagnostic tool in selecting young swimmers.